Distinct Patterns of Tryptophan Maintenance in Tissues during Kynurenine Pathway Activation in Simian Immunodeficiency Virus-Infected Macaques - Drewes, Julia L.; Croteau, Joshua D.; Shirk, Erin N.; Engle, Elizabeth L.; Zink, M. C.; Graham, David R. (Frontiers in Immunology, 2016)
Induction of the kynurenine pathway (KP) of tryptophan catabolism has been proposed to contribute to T cell dysfunction during human/simian immunodeficiency virus (HIV/SIV) infection via depletion of local tryptophan levels and production of immunomodulatory KP metabolites. However, while changes in tryptophan and KP metabolites have been observed in plasma, their levels in lymphoid tissues and levels of enzymes downstream of indoleamine 2,3-dioxygenase (IDO1) have been relatively unexplored. We used our SIV-infected pigtailed macaque model to analyze longitudinal changes in KP metabolites and enzymes by gas chromatography/mass spectrometry and NanoString nCounter gene expression analysis, respectively, in spleen and blood compared to changes previously established in brain and CSF. We found that tryptophan levels were remarkably stable in tissue sites despite robust depletion in the circulating plasma and CSF. We also demonstrated that intracellular tryptophan reserves were maintained in cultured cells even in the presence of depleted extracellular tryptophan levels. Kynurenine, 3-hydroxykynurenine, quinolinic acid, and the KP enzymes all displayed highly divergent patterns in the sites examined, though IDO1 expression always correlated with local kynurenine/tryptophan ratios. Finally, we demonstrated by FACS that myeloid dendritic cells (mDCs) and cells of monocytic lineage were the highest producers of IDO1 in chronically infected spleens. Overall our study reveals insights into the tissue-specific regulation of KP enzymes and metabolites and, in particular, highlights the multiple mechanisms by which cells and tissues seek to prevent TRP starvation during inflammation.